A New Genus of Endomychinae (Coleoptera: Endomychidae) from the Neotropics with Unusual Mouthparts - Arriaga-Varela, E; Tomaszewska, W; Fikáček, M (Neotropical entomology, 2019)
Tharina gen. nov. along with T. antennalis (as type species), T. ecuadoriensis, T. micra, and T. peckorum spp. nov. (Coleoptera: Endomychidae: Endomychinae) from Venezuela, Ecuador, and Bolivia are described, diagnosed, and illustrated. Mouthpart structures, in this genus, which are unique within the family Endomychidae, are discussed in terms of their function. Notes on the unusual female genitalia in one species are provided.
Keywords: Taxonomy; Bolivia; Bolívie; Tharina; Coccinelloidea; Venezuela; Female; Beetles; Genitalia, Female; zvířata; Coleoptera; Ecuador; ženské pohlaví; Male; ženské pohlavní orgány; Ekvádor; brouci; Animals; mužské pohlaví